Identifikasi Ukuran Luas Tanah dengan Mengimplementasikan Metode Transformasi Watershed - Yoga Saputra; Yovi Apridiansyah; Ardi Wijaya (JSAI (Journal Scientific and Applied Informatics), 2024)
This study discusses the application of the watershed transformation method to measure land area in satellite images. The main objective is to improve the accuracy of land area measurement, which is important for various applications such as agriculture, urban development, and nature conservation. Given its often time-consuming and resource-intensive nature, this study aims to develop a more efficient and faster method of processing satellite image data. The method starts with the collection and pre-processing of satellite image data to improve its quality. Next, watershed transformation is applied for image segmentation and land area measurement. The results are evaluated through accuracy analysis and comparison with reference data. From testing 20 sample data, Precision of 100%, Recall of 80%, and Accuracy of 95% were obtained. It is expected that this research can contribute to the development of a more efficient and reliable land area measurement technique.